2021
DOI: 10.1109/tnsre.2021.3068453
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Evaluation of Dynamic Splint Based on Pulley Rotation Design for Management of Hand Spasticity

Abstract: A dynamic splint is superior to traditional static splint, offering more benefits such as reduced spasticity, allowing comfortable stretch, repositioning fingers in extension positions, and increasing hand performance. This paper suggested the development of a dynamic splint based on a pulley rotation with a locking system as a home rehabilitation device to reduce hand spasticity in stroke patients. Moreover, this study consisted of two main activities: simulation using finite element analysis and clinical exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 36 publications
0
9
0
1
Order By: Relevance
“…Several previous studies have described a variety of dynamic splints that effectively improved motor function and relieved spasticity in stroke patients [ 16 , 17 , 32 , 42 ]. In comparison to a static splint, a dynamic splint consists of a static base that forms the foundation of the splint, and an outrigger, the mobile part consisting of levers, springs, or pulleys.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several previous studies have described a variety of dynamic splints that effectively improved motor function and relieved spasticity in stroke patients [ 16 , 17 , 32 , 42 ]. In comparison to a static splint, a dynamic splint consists of a static base that forms the foundation of the splint, and an outrigger, the mobile part consisting of levers, springs, or pulleys.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the fingers could be stretched in extension with the wrist, extended by a simple locking mechanism for a prolonged time. Our previous study had shown that stretching three fingers (thumb, index, and middle fingers) reduced the finger flexors’ spasticity, and the splint was easy to self-use at home [ 32 ]. Therefore, we used a 3D-printed dynamic splint with a novel three-finger design in the current study.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The limitation of joint range of motion and exaggeration of stretch reflexes increase with the severity of spasticity [1], which impacts the life quality for stroke patients and brings challenges to rehabilitation therapies. Previous studies demonstrated that comprehensive evaluation of spasticity improved the efficiency of rehabilitation [2], [3]. Conventionally, the most commonly used spasticity measurement methods in practice are clinical scales, e.g., Modified Ashworth Scale (MAS) [4], [5], and Australian Spasticity Assessment Scale (ASAS) [6].…”
Section: Introductionmentioning
confidence: 99%